2016
DOI: 10.1155/2016/2187275
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and Clinical Outcome of Intracranial Aneurysms after Treatment Using Flow Diverter Devices: Mid-Term Follow-Up

Abstract: Flow diverters (FDs) are designed for the endovascular treatment of complex intracranial aneurysm configurations. From February 2009 to March 2013 28 patients (22 females, 6 males) were treated with FD; mean age was 57 years. Data, including aneurysm features, clinical presentation, history of previous bleeding, treatment, and follow-up results, are presented. Early postinterventional neurological deficits (transient: n = 3/enduring: n = 1) appeared in 4/28 patients (14%), and early improvement of neurological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…One study found that all patients were among the expected antiplatelet inhibition rate 33. The remaining studies did not report complications based on antiplatelet testing results, but 20 studies reported the action taken after abnormal results: two studies reported postponing procedures,34 35 three reported modification of the loading dose,36–38 eight reported switching to prasugrel/ticagrelor regimens,14 39–45 and seven studies reported switching to an alternative regimen 46–52. Another eight studies (335 patients) did not conduct antiplatelet testing at all and nine studies with 406 patients did not report the data on its usage (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…One study found that all patients were among the expected antiplatelet inhibition rate 33. The remaining studies did not report complications based on antiplatelet testing results, but 20 studies reported the action taken after abnormal results: two studies reported postponing procedures,34 35 three reported modification of the loading dose,36–38 eight reported switching to prasugrel/ticagrelor regimens,14 39–45 and seven studies reported switching to an alternative regimen 46–52. Another eight studies (335 patients) did not conduct antiplatelet testing at all and nine studies with 406 patients did not report the data on its usage (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In doubtful cases, we suggest consideration of other invasive treatment methods, e.g. microsurgical clipping, bypass surgery, and other methods of proven efficacy, which might be beneficial for a patient [ 21 - 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is mounting evidence showing favorable technical success and safety profile of flow diversion, as well as emerging long-term data suggesting efficacy. 1,[6][7][8][9][10][11][12][13][14] However, the presence of a pre-existing stent 6 or an incorporated branch arising from the aneurysm [1][2][3][4] have been identified as potential factors for delayed or failed aneurysm occlusion. This study investigated branch artery relative size and geometry as risk factors for delayed aneurysmal occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have suggested a relationship between delayed occlusion of intracranial aneurysms treated with the Pipeline Embolization Device (PED; Covidien-Medtronic, Irvine, CA) and the presence of an incorporated branch, regardless of aneurysmal location. [1][2][3][4][5] In some cases, however, flow diversion may still represent the preferred treatment modality, such as in cases of difficult surgical access or branch vessel incorporation into the aneurysm precluding standard or adjunctive coiling. In situations of delayed aneurysm occlusion with branch incorporation, careful inspection of the catheter angiograms often demonstrates the appearance of abnormal flow of contrast through the aneurysm body ''entry remnant'' and then into the incorporated branch.…”
Section: Introductionmentioning
confidence: 99%